УЧАСТЬ ЖІНОК В УКРАЇНСЬКОМУ ПРОТЕСТАНТСЬКОМУ РУСІ 20-х рр. ХХ ст. ЗА МАТЕРІАЛАМИ УКРАЇНСЬКИХ ПРОТЕСТАНТСЬКИХ ЖУРНАЛІВ (Zaporizhzhia Historical Review, 2021)
The role of the Protestantís magazines of the 20-th years XX c. about the stirring up of the religious creative work of women and their Orthodox service is been analyzed. The forms of the spiritual initiative of women in the community ñ Baptists, Реntecostal evangelic, Adventists of the gospel believe are been lighted.